Mental Health Services in Colombia: A National Implementation Study - Rojas-Andrade, R (SAGE Publications Inc., 2023)
Laws in Latin American countries are based on scientific evidence that calls for mental health services to move to the community. These care modalities have implementation problems. The objective of this article is to describe the implementation of the services proposed in Law 1616 of 2013 of Colombia (Mental Health Law): emergencies, hospitalization, community-based rehabilitation, pre-hospital care, day hospital for children and adults, Drug Addiction Care Center, groups support and mutual aid, telemedicine, and home and outpatient care. We used a mixed study, with a cross-sectional descriptive quantitative component, where an instrument was used to determine the level of implementation of these services, consisting of a scale that established the availability and use of these services, in addition to the climate of implementation of the services and community mental health strategies, in addition to a qualitative determination of barriers and facilitators of implementation. We found a low availability of all services in departments such as Amazonas, Vaupés, Putumayo, and Meta and an implementation of services in Bogotá and Caldas. The least implemented services are the community ones, and those with the greatest presence at the territorial level are emergencies and hospitalization. We conclude that low- and middle-income countries have few community models and invest a large part of their technical and economic effort in emergencies and hospitalization. There are difficulties in the implementation of most of the services proposed by Colombian legislation related to mental health. © The Author(s) 2023.